PERTANGGUNGJAWABAN BANK SEBAGAI KORPORASI TERHADAP TERJADINYA FRAUD - Adi Atmaka; Martin Roestamy (Magister Hukum Sekolah Pascasarjana Unida, 2019)
Operations of crimes committed by bank burglars must be immediately anticipated by the legal apparatus in Indonesia quickly and carefully so that the law does not look weak. At present the development of criminal legal responsibility has begun to expand, in the concept of criminal law, accountability can not only be requested from individuals, but also corporately. The obstacle is the concept of accountability of various corporate modes of law enforcement in Indonesia, so far it has not been utilized, besides the concept of corporate responsibility is not yet widely known, this concept is also still in the gray domain. Identification of this research are: 1) How is the bank's responsibility as a corporation for fraud and fraud ?. 2) What is the legal protection of bank customers who are victims of fraud? The research method used in this study is a normative juridical approach. The results of this study are: 1) Bank Indonesia as the holder of the Indonesian banking authority in an effort to meet applicable standards in the banking sector has prioritized programs related to customer protection, handling customer complaints, and including handling the establishment of independent banking mediation institutions, 2) In banking practice, a provision applies that customers who will save their funds in a bank are not free. The customer has the right to receive interest on funds deposited with the bank.